2020
DOI: 10.1111/dmcn.14613
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐dopamine D2 receptor antibodies in chronic tic disorders

Abstract: Aim To investigate the association between circulating anti‐dopamine D2 receptor (D2R) autoantibodies and the exacerbation of tics in children with chronic tic disorders (CTDs). Method One hundred and thirty‐seven children with CTDs (108 males, 29 females; mean age [SD] 10y 0mo [2y 7mo], range 4–16y) were recruited over 18 months. Patients were assessed at baseline, at tic exacerbation, and at 2 months after exacerbation. Serum anti‐D2R antibodies were evaluated using a cell‐based assay and blinded immunofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…While changes in D2‐autoantibodies expression may be purely epiphenomenal, 3 extant evidence seems consistent with a role of D2 autoantibodies in the pathophysiology of CTDs. It will be extremely interesting to test whether that is truly the case and whether D1 autoantibodies are also similarly implicated, even if through different mechanisms.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…While changes in D2‐autoantibodies expression may be purely epiphenomenal, 3 extant evidence seems consistent with a role of D2 autoantibodies in the pathophysiology of CTDs. It will be extremely interesting to test whether that is truly the case and whether D1 autoantibodies are also similarly implicated, even if through different mechanisms.…”
mentioning
confidence: 70%
“…Addabbo et al address the link between the (detectable) expression of serum dopamine‐D2‐receptor autoantibodies and tic‐severity fluctuations in children with CTDs, 3 using a well‐validated cell‐based assay 4 . Consistent with previous studies on CTDs and, for example, acute‐onset psychosis, the authors show that, in their patient cohort, periods of symptom exacerbation, like periods of post‐exacerbation (approximately 2 months after), were both selectively associated with increases in the expression of D2 autoantibodies for 8% of the patients (11/137 and 9/112 of the patients with data respectively) 3 . Given that the authors controlled for possible confounds and that medication usage, like other clinical and demographical features, did not differ between patients who had and who had no detectable variations in the expression of D2 autoantibodies over time, the reported results might conceivably suggest that, in some patients with CTDs, D2 autoantibodies can exacerbate symptoms.…”
mentioning
confidence: 99%
“…Dale et al ( 102 ) demonstrated the presence of anti-D 2 dopamine receptor (D 2 R) antibodies in the serum of 4 of 44 TS patients, using FACS applied on human embryonic kidney (HEK) cells transfected with a commercial form of the D 2 R; none of these 44 patients were positive for anti-D 1 dopamine receptor antibodies. Very recently, Addabbo et al ( 103 ) tested anti-D 2 R antibody reactivity in sera from 137 children with TS at a baseline time point and at time points coinciding with and following a clinically relevant tic exacerbation. These authors used a similar protocol to the one used by Dale et al ( 102 ), but adopting a transfection method on Chinese Hamster Ovary (CHO)-K1 cells ( 102 ).…”
Section: Immune-inflammatory Markers (See Table 1 mentioning
confidence: 99%
“…An earlier cross-sectional report on 51 patients with TS did not detect any specific serum autoantibodies associated with encephalopathies (targeting LGI1, CASPR2, NMDAR, AMPA1/2, GABAB1/B2) ( 104 ). More recently, Baglioni et al ( 105 ) investigated the same patients tested by Addabbo et al ( 103 ) plus a cohort of unaffected siblings of these patients, screening for autoantibodies associated with established encephalopathies (antibodies targeting NMDAR, CASPR2, LGI1, AMPAR, and GABAAR). Using live cell-based assays applied to live rat hippocampal neurons, only two individuals (one patient, one sibling) tested weakly positive for anti-NMDAR antibodies, indicating unlikely association with these pathogenic antibodies.…”
Section: Immune-inflammatory Markers (See Table 1 mentioning
confidence: 99%
“…These include disorders with a well-recognised autoimmune aetiology, such as Sydenham's chorea and basal ganglia encephalitis, and also neuropsychiatric and neurodevelopmental disorders, such as first episode of psychosis, Tourette's syndrome and paediatric acute-onset neuropsychiatric syndrome (PANS). [12][13][14][15][16][17][18][19] The precise mechanisms underlying autoimmunity in these disorders remain unclear, but it has been postulated that D2R antibodies may alter dopaminergic signalling by stimulating excess dopamine secretion, 20 inducing inhibitory D2R signalling 16 and triggering receptor internalisation. 19 Additionally, D2R antibodies can be useful in identifying patients who can be amenable to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%